DETERMINASI PENDAPATAN UMKM DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG DALAM PERSPEKTIF EKONOMI MIKRO: Determinants Of Umkm Income In Abiansemal Subdistrict, Badung Regency From A Microeconomic Perspective - Ayuk, Ni Made Taman; Yasmita, I Gusti Ayu Lia; Kusmawan, I Made Hary (Ganec Swara, 2026)
The purpose of this study is to analyze the effect of labor, capital, and business duration, both partially and simultaneously, on the income of MSMEs in Abiansemal District, Badung Regency. The sample used in this study consists of 99 MSME units. The sampling method applied is simple random sampling. Data analysis is conducted using multiple linear regression analysis. The results of the partial hypothesis testing indicate that labor, capital, and business duration have a positive and significant effect on the income of MSMEs in Abiansemal District, Badung Regency. Furthermore, simultaneously, these three variables are also proven to have a significant effect on MSME income in the area.